Expression of truncated PrP targeted to Purkinje cells of PrP knockout mice causes Purkinje cell death and ataxia - Flechsig, Eckhard (Oxford University Press, 2003)
PrP knockout mice with disruption of only the PrP-encoding region (Zürich I-type) remain healthy, whereas mice with deletions extending upstream of the PrP-encoding exon (Nagasaki-type) suffer Purkinje cell loss and ataxia, associated with ectopic expression of Doppel in brain, particularly in Purkinje cells. The phenotype is abrogated by co-expression of full-length PrP. Doppel is 25% similar to PrP, has the same globular fold, but lacks the flexible N-terminal tail. We now show that in Zürich I-type PrP-null mice, expression of N-terminally truncated PrP targeted to Purkinje cells also leads to Purkinje cell loss and ataxia, which are reversed by PrP. Doppel and truncated PrP probably cause Purkinje cell degeneration by the same mechanism.